Estudio etológico de la cerda y sus lechones en una maternidad funcional con energía renovable - Montalbán Chininín, César Agusto (2025)
This study evaluated the behaviour of the sow and her piglets, housed in two types of farrowing pens (n=3). Maternity pen built of noble material with cement feeder and nipple-type drinker with a crib that provided heating to the piglets with electric energy sources (Floor) and a cage-type farrowing pen (Cage) with functional ventilation with surface geothermal energy (heat exchange at 3 m depth) and solar panels that supply energy to the fans and the crib to provide heating. Video cameras recorded 24 h a day for 27 days (farrowing to weaning), to evaluate the body positions of the sow (lying down, standing, sitting) and the activity of the piglets (inside the crib, outside the crib suckling, and outside the crib not suckling). Sows in crates spent more time in the lying position (p<0.01) and less time in the standing (p<0.01) and sitting (p<0.01) positions compared to those in floor farrowing. Piglets from sows housed in cages spent more time inside the crib (p<0.05), while the time spent outside the crib suckling during the day was similar in both farrowing units (p>0.05). However, at night, piglets from sows in floor farrowing units spent more time outside the crib suckling. The longer time spent in the resting position (lying) of the sow and the longer time spent by piglets in the crib suggest that the functional farrowing unit with geothermal and photovoltaic energy provides a comfortable environment for the pig.